Manganese – a promising element also in high alloy sintered steels. (15th March 2021) - Danninger, Herbert; Gierl-Mayer, Christian; Prokofyev, Mikhail; Huemer, Marie-Christine; de Oro Calderon, Raquel; Hellein, Robert; Müller, Alexander; Stetina, Gerold
ABSTRACT: Manganese is a standard alloy element in many wrought steels, offering improved strength and hardenability and, in Hadfield steels, also a unique combination of strength, ductility and work hardening behaviour. In sintered steels Mn has been used rarely so far because of two reasons: one is the high oxygen affinity of Mn which promotes oxygen pickup during heat treatment and inhibits removal of oxygen in part through the 'internal getter' effect. The other reason is the high vapour pressure of Mn which results in Mn loss during sintering. In this presentation, these problems are discussed on Mn-alloyed sintered steels with transformation-induced plasticity behaviour. It is shown that by suitable alloying techniques, combined with adjustment of the manufacturing parameters, the problems can be overcome and the benefits of Mn addition can be reaped, obtaining PM steels for which potentially surface densification and hardening can be attained in one run.